Beleza digital na plataforma Instagram: uma análise da influência dos filtros na construção da identidade e cidadania comunicativa feminina - Silva, Jóice Cristiane da (Universidade do Vale do Rio dos Sinos, 2024)
The central theme of this study is an in-depth understanding of the influences of beauty filters on Instagram on the definition of beauty, female identity and communicative citizenship. The general objective is to analyze how beautifying filters and the possibilities of editing photos on Instagram have an impact on the way women define what is beautiful, and how they construct their communicative citizenship. The specific objectives are (a) to analyze how Instagram contributes to the formation of beauty standards and female identity in the current context; (b) to problematize how these communicating subjects define what is beautiful and materialize it through their posts on the Instagram platform; (c) to investigate how communicative citizenship is influenced by the use of filters on Instagram, considering self-image and the meaning of beauty for women; (d) explore women's perception of the representativeness of different bodies, ethnicities and ages on social media, in order to understand how these standards impact the diversity of conceptions of beauty; and (e) analyze the role of research and personal reflection in the researcher's training as a professional, thinker and agent of transformation in the field of communication sciences. The research problem proposed for the study was: "how Instagram's photo filters and editing possibilities affect the way women define beauty and construct their identity. How can the sight of their own edited image change their perception of beauty and create a material desire to turn the image into reality?" To this end, the exploratory and descriptive method was used, through a literature review, documentary research and ethnographic research in a digital environment, with the application of two collection instruments, namely questionnaires and interviews. The data obtained from the interviews was analyzed qualitatively, using in-depth content analysis, and the questionnaires were treated qualitatively and quantitatively using discourse and content analysis. The results obtained suggest that the construction of female identity is an intricate process, influenced by various factors beyond just physical appearance. Valuing diversity and deconstructing unrealistic beauty standards are highlighted as essential elements for building a healthier and more positive identity. Observing ambiguities in women's communication on social media reveals a notable insecurity associated with the use of these platforms. Although some women claim not to be affected, the analysis indicates that, within the dynamics of digital interactions, there is a significant influence on the adoption of standards suggested by the platform itself. The dichotomy between self-perception of resistance to external influence and evidence of compliance with the platform's expectations highlights the complexity of online interactions and their implications for the construction of women's digital image. This scenario highlights the importance of questioning and putting established standards into crisis, recognizing the multiplicity of perspectives and the need for a critical approach to influences on social networks.
Keywords: Mulheres; Padrões de beleza; Instagram; Filtros; Edição de fotos; Cidadania comunicativa; Women; Beauty standards; Filters; Photo editing; Communicative citizenship; ACCNPQ::Ciências Sociais Aplicadas::Comunicação